1996
DOI: 10.1177/1045389x9600700213
|View full text |Cite
|
Sign up to set email alerts
|

Performance of a Smart Vibration Isolator for Precision Spacecraft Instruments

Abstract: This paper describes the configuration and measured performance of an hybrid, active-passive vibration isolation mount designed to mitigate vibratory disturbances on sensitive spacecraft instruments. The device, called the Active Vibration Canceler (AVC), consists of a passive isolation stage using composite leaf springs faced with shape-memory metal sheet material to provide load-adaptive damping, and an active, force-canceling stage using a motion-amplified electrostrictive stack actuator to augment attenuat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

1998
1998
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 5 publications
0
11
0
Order By: Relevance
“…However, equation (16) shows that this amount is effectively reduced when the feedforward sensor is used. Of course, the effective reduction is a function of the relative``quality'' of the feedforward measurement, given by V ms .…”
Section: Vibration Isolation 29mentioning
confidence: 97%
See 1 more Smart Citation
“…However, equation (16) shows that this amount is effectively reduced when the feedforward sensor is used. Of course, the effective reduction is a function of the relative``quality'' of the feedforward measurement, given by V ms .…”
Section: Vibration Isolation 29mentioning
confidence: 97%
“…This analysis can also be applied to the typical engineering problem of actively isolating a payload from the vibrations of a moving platform (see reference [16], for example). In this case active controller design ®ts into the hybrid control architecture when both the platform and the isolation mass are equipped with displacement sensors that have signi®cant dynamics.…”
Section: Example: Isolation System With Sensor Dynamicsmentioning
confidence: 99%
“…In this manner, Regelbrugge et al (1996) have shown that efficient vibration amplitude reduction is accomplished without the cost of an active system. Furthermore, Webster and Semke (2004) have demonstrated that enhanced performance is attained with the use of frequency-dependent viscoelastic structural components.…”
Section: Introductionmentioning
confidence: 95%
“…For example, PMN-PT multilayered actuators were recently used in an active mirror positioning mechanism, which was part of the optical scheme for correcting the Hubble Space Telescope's spherical aberration [8]. Researchers also have examined PMN-PT for active vibration isolation of spacecraft systems [9] and underwater sonar applications [10], [11].…”
Section: Introductionmentioning
confidence: 99%